Researches on ovine adenavirus type three (oa3) isolated from clinically healthy sheep in turkey - Feridun ÖZTÜRK (Eurasian Journal of Veterinary Sciences)
A cytopathogen virus isolated by means of MDBK (Madin Darby Bovine Kidney) and primary lamb kidney tissue cultures from the faeces of clinically healthy sheep brought to Meat and Fish Organization Ankara. Isolated virus was alsa able to multiply in cattle originated cells besides the sheep originated ones and the type of its nucleic acid was DNA. According to measurements made by electronmicroscope its length was alıout 100 milimicron. It was resisted against fat soluables such as ethe.r and chloroform and also trypsin enzyme. It lost infectiousness at 56°C in 120 minutes and at 60°C in 30 minutes. In between 3.0 and 4.0 pH degrees its infectiousness estimated to be decreased. It gave heamagglutination with rat erythrocytes and no elinical syımptoms estimated in rabbit, quinea pig and mice, but neutralizing antibodies were estimated in rabbit and quinea pig. Neutralisation estimated with OA3 by means of cross neutralisation. It is concluded that the isolated virus was ovine adenavirus type 3 (OA3) in accordance to the characteristics mentioned above.